Airborne Infection Control measures among Government and Private Health Facilities in a hilly district of North India - Kumar, Mohinder; Vohra, Jai Gopal; Pathania, Abhishek; Singh, Gurmeet (Indian Journal of Community Health, 2024)
Introduction: Guidelines for Airborne Infection Control in Health Care Settings were published in the 2010 to reduce Airborne Infections in health service providers and visitors to health facilities. Objectives: To evaluate healthcare facilities regarding implementation of Guidelines for Airborne Infection Control in Health Care Settings. Methods: An analytic, cross- sectional, health care facility-based study in the district Solan of Himachal Pradesh. A total 53 health care facilities from both public and private sectors were assessed and compared. Results: The implementation of these guidelines was unsatisfactory. Government health care facilities were better implementing the guidelines, compared to the private sector. Conclusion: The guidelines are over a decade old and implementation is not optimal. Efforts and emphasis are required to be put into implementation of these guidelines in health care facilities. An update of policy with stringent penalties are advocated for better compliance in the private sector.